Fluorohydration of alkynes via I(I)/I(III) catalysis - Neufeld, Jessica; Daniliuc, Constantin G.; Gilmour, Ryan (Beilstein Journal of Organic Chemistry, 2020)
Substrate specificity is ubiquitous in biological catalysis, but less pervasive in the realm of small-molecule catalysis. Herein, we disclose an intriguing example of substrate specificity that was observed whilst exploring catalysis-based routes to generate α-fluoroketones from terminal and internal alkynes under the auspices of I(I)/I(III) catalysis. Utilising p-TolI as an inexpensive organocatalyst with Selectfluor® and amine/HF mixtures, the formation of protected α-fluoroketones from simple alkynes was realised. Whilst the transient p-TolIF2 species generated in situ productively engaged with pentynyl benzoate scaffolds to generate the desired α-fluoroketone motif, augmentation or contraction of the linker suppressed catalysis. The prerequisite for this substructure was established by molecular editing and was complemented with a physical organic investigation of possible determinants.
Keywords: α-fluoroketone; alkyne; fluorination; hypervalent iodine; organocatalysis